ANALISIS GAYA BAHASA PADA PUISI “KANGEN” KARYA W.S. RENDRA - Trisnawati (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2022)
Poetry is a literary work that contains the outpouring of the heart or the expression of feelings with imaginative words that are poured into a piece of writing. Poetry is bound by rhythm, dimension, rhyme, as well as the arrangement of lines and stanzas. This article discusses the meaning of the poem "Kangen" by WS. Rendra uses a metaphorical figure of speech. In addition, W.S. Rendra packs poetry with a very modern style of writing and there is a typographical style of writing. This study uses a qualitative descriptive method. This study focuses on the style of language used and the analysis of the meaning of the poem.